Neurological Complications in Thyroid Surgery: A Surgical Point of View on Laryngeal Nerves - Varaldo, Emanuela; Ansaldo, Gian Luca; Mascherini, Matteo; Cafiero, Ferdinando; Minuto, Michele N. (Frontiers in Endocrinology, 2014)
The cervical branches of the vagus nerve that are pertinent to endocrine surgery are the superior and the inferior laryngeal nerves: their anatomical course in the neck places them at risk during thyroid surgery. The external branch of the superior laryngeal nerve (EB) is at risk during thyroid surgery because of its close anatomical relationship with the superior thyroid vessels and the superior thyroid pole region. The rate of EB injury (which leads to the paralysis of the cricothyroid muscle) varies from 0 to 58%. The identification of the EB during surgery helps avoiding both an accidental transection and an excessive stretching. When the nerve is not identified,the ligation of superior thyroid artery branches close to the thyroid gland is suggested, as well as the abstention from an indiscriminate use of energy-based devices that might damage it. The inferior laryngeal nerve (RLN) runs in the tracheoesophageal groove toward the larynx, close to the posterior aspect of the thyroid. It is the main motor nerve of the intrinsic laryngeal muscles, and also provides sensory innervation to the larynx. Its injury finally causes the paralysis of the omolateral vocal cord and various sensory alterations: the symptoms range from mild to severe hoarseness, to acute airway obstruction and swallowing impairment. Permanent lesions of the RNL occur from 0.3 to 7% of cases, according to different factors. The surgeon must be aware of the possible anatomical variations of the nerve which should be actively searched for and identified. Visual control and gentle dissection of RLN are imperative. The use of intraoperative nerve monitoring has been safely applied but, at the moment, its impact in the incidence of RLN injuries has not been clarified. In conclusion, despite a thorough surgical technique and the use of intraoperative neuromonitoring, the incidence of neurological complications after thyroid surgery cannot be suppressed, but should be maintained in a low range.